Kes perniagaan Sabah : kajian intensification of research in priority areas (lRPA) - Siti Maimon Hj. Kamso; Wajiran Sinun; Darwis Awang; Arsiah Hj Bahron; JANE CHANG YANN CHIN; Chang, Jane Yann Ching; Chan, Jennifer Kim Lian; Kalsom Abdul Wahab; Mohd. Khairi Ismail; Ratnawati Osman; Sarma Aralas; Sharija Che' Shaari; et al. (Universiti Malaysia Sabah, 1997)
No. abstract